2021
DOI: 10.1021/acs.est.1c00349
|View full text |Cite
|
Sign up to set email alerts
|

Silicate-Enhanced Heterogeneous Flow-Through Electro-Fenton System Using Iron Oxides under Nanoconfinement

Abstract: Herein, a silicate-enhanced flow-through electro-Fenton system with a nanoconfined catalyst was rationally designed and demonstrated for the highly efficient, rapid, and selective degradation of antibiotic tetracycline. The key active component of this system is the Fe2O3 nanoparticle filled carbon nanotube (Fe2O3-in-CNT) filter. Under an electric field, this composite filter enabled in situ H2O2 generation, which was converted to reactive oxygen species accompanied by the redox cycling of Fe3+/Fe2+. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(70 citation statements)
references
References 46 publications
0
69
0
Order By: Relevance
“…In contrast, the removal efficiency decreased by 31% in the control system of the nonconfined Co nanoparticles. Besides, the catalytic activity and stability was improved by using the nanoconfined yolk–shell system. Moreover, the nanoscale interior cavity is likely to change the product distribution, which has been validated in various reactions in organic synthesis. An example in the wastewater treatment is from Li’s group that phenol was selectively oxidized to maleic acid by HO • in the nanoconfined space …”
Section: Selective Oxidation Via Tuning the Accessibility Of Targets ...mentioning
confidence: 99%
“…In contrast, the removal efficiency decreased by 31% in the control system of the nonconfined Co nanoparticles. Besides, the catalytic activity and stability was improved by using the nanoconfined yolk–shell system. Moreover, the nanoscale interior cavity is likely to change the product distribution, which has been validated in various reactions in organic synthesis. An example in the wastewater treatment is from Li’s group that phenol was selectively oxidized to maleic acid by HO • in the nanoconfined space …”
Section: Selective Oxidation Via Tuning the Accessibility Of Targets ...mentioning
confidence: 99%
“…Wu et al ( Wu et al, 2016 ) removed bisphenol A and norfloxacin from drinking water using acid-treated CNTs and polyvinyl chloride ultrafiltration membranes. Guo et al designed a silicate-enhanced fluidized electro-Fenton system with a nanoconfined catalyst for the removal of tetracycline ( Guo et al, 2021 ). Zheng et al designed an electrocatalytic filtration system with carbon nanotube supported nanoscale zerovalent copper toward ultrafast oxidation of organic pollutants ( Zheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 . The anti-COVID-19 degradation kinetics at alkaline pH conditions could be attributed to the reduced H 2 O 2 decomposition to produce the reactive oxygen species (ROS) ( Guo et al, 2021 ). The results revealed that the k constantly decreased with increasing pH.…”
Section: Resultsmentioning
confidence: 99%